Análise econômica e funcional da água das Barragens de Faveta e Salineiro em Santiago - Cabo Verde - Moura, Miguel Ângelo Barreto da (2015)
The surface dams have been adopted by the Government Cape Verde Republic, as part of its efforts in order to face the water scarcity in this archipelago. The country´s first surface dam was built on 2005, at the Ribeira Seca Hydrographic Catchment which is located in Santiago. However, since then, two more surface dams has constructed; one in Faveta, and another one in Salineiro, as part of the Government efforts to maximize the country´s surface water potential, which is evaluated as of 124 million cubic meter per year. The dam in Faveta was designed catch and distributes water enough in order to irrigate thirty hectares of farming land to benefit directly the villagers of Faveta and Achada Leitão, both hem in São Salvador do Mundo Municipality. The Salineiro surface dam also was designed to provide enough water to irrigated 58 hectares of farming land, in order to benefit the villagers of Salineiro and Calabaceira, both in Ribeira Grande Municipality. When operational these two surface dams can provide water which will be enough to irrigate some 88 hectares of farming land. Traditionally, the country´s authorities used to evaluate the economic feasibility of country´s water facilities, by using the financial approaches, which can hide the water potential cost of potential inefficient uses. However some has adopted the economic approaches as tool to evaluate the best options in water allocation, ignoring the fact that water physical attributes and water economic characteristics differed from other market goods and services. The occurrence of water benefits might be not follow a deterministic path, but random ones, which might also depend of the way the water functions is combined in order to provide good and services which can profited by the society. The research aims to present and discuss a methodology that can be used to perform the quantification of the amount of water full cost and water full economic values (Rogers et al 1998). In this thesis, the traditional economic deterministic approaches were substituted by a random economic approach (Lee & James 1971) and Vieira (2005). By using an hydrological model VYELAS (Araújo, 2006) the water balance was calculated as well as the water availability, and water yield was also computed. The results which were accomplished showed that water benefits were sensible the variations in water yield. The conclusions of this research also show that an integrated approach in water resources management can optimized better the social liquid benefits of water